Metacognitive awareness components of high-academic ability students in biology hybrid learning: Profile and correlation - Iin Hindun; N. Nurwidodo; Azizul Ghofar Candra Wicaksono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Metacognitive awareness has been considered as one of the factors within students that determines learning success. It can be developed through a hybrid learning approach. The purpose of this quantitative research was to examine the metacognitive awareness profile of students with high-academic ability in hybrid learning implementation. The subjects of this study were the students of XI-Science class of state senior high school of Malang. The Metacognitive Awareness Inventory was used as the data collection instrument, while descriptive statistics and Pearson Product-Moment were chosen as the data analysis techniques. The results of the study informed that the students’ metacognitive awareness was divided into four categories, i.e. very good (9%), good (43%), enough (46%), and very low (2%). The three components of metacognitive awareness were classified as "enough", while the five components of students were categorized as "good". The eight metacognition components showed significant correlations each other (r > 0.41, n = 55, p < 0.01). It can be concluded that the majority of students’ metacognitive awareness was satisfactory even though there were a small proportion of students whose metacognitive awareness was not good.